Creativity as a transforming element of the territory: La Cárcel_ Segovia Creaction Center - Rodrigo-Martín, Luis; Núñez-Gómez, Patricia (Street Art & Urban Creativity, 2025)
This research addresses the transformative power of creativity in the construction of sociocultural and symbolic meanings. Using a qualitative, descriptive, analytical, and conclusive methodology, based on the analysis of multiple cases in combination with the analysis of a particular case, the study analyzes the re-signification of places associated with suffering, pain, and deprivation of liberty in antagonistic settings characterized by well-being, progress, and freedom. A case study is carried out: “La Cárcel_Segovia Centro de Creación” (The Prison_Segovia Creation Center), which studies the reconfiguration of the former Provincial Prison of Segovia into a multidisciplinary space aimed at promoting artistic creation and socioeconomic development through the promotion of creative industries and the improvement of public space. The results demonstrate the importance of creativity for the social, cultural, and economic development of territories.